Interview of María Soledad Cisternas Reyes and Rosa Kornfeld‑Matte - Cisternas Reyes, María; Kornfeld-Matte, Rosa (Aequitas, 2023)
This interview was prepared, conducted, and reviewed by Marion Scheider-Yilmaz, post-doctorate researcher at PACTE, University of Grenoble Alpes and Jean-Philippe Viriot Durandal, Professor at the University of Lorraine and “Inclusive society and ageing” chairholder. The aim was to hear from María Soledad Cisternas Reyes, Special Envoy on Disability and Accessibility for the UN (2017 – June 2023), and Rosa Kornfeld-Matte, Independent Expert on the enjoyment of all human rights by older persons by the UN Human Rights Council (2014 – 2020), about their commitment to the inclusion and promotion of the rights of persons with disabilities and older persons. Throughout the discussion, the process that led to the promulgation of the Convention on the Rights of Persons with Disabilities is presented. Based on this historical example, the ongoing challenges in the process in favor of a Convention on the rights of older people are then outlined.